2004
DOI: 10.1525/can.2004.19.3.365
|View full text |Cite
|
Sign up to set email alerts
|

The Productive Life of Risk

Abstract: Contemporary social theorists usually conceive of risk negatively. Focusing on disasters and hazards, they see risk as an object of calculation and avoidance. But we gain a deeper understanding of risk in modern life if we observe it in another setting. Futures markets are exemplary sites of aggressive risk taking. Drawing upon extensive fieldwork on trading floors, this article shows how a high modern institution creates populations of risk‐taking specialists, and explores the ways that engagements with risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(85 citation statements)
references
References 27 publications
(10 reference statements)
0
83
0
2
Order By: Relevance
“…Since its inception, petroleum exploration has combined the bold assessments of oilmen with the speculative fantasies of urban financiers and the hypothetical inferences of a new breed of geoscientists in what an oil executive of the time called "the gamble of drilling for oil" (Zimmermann 1933, 500;Lucier 2008). Speculation, in this sense, exceeds its narrower, contemporary definition of a type of behavior pertaining exclusively to the domain of finance (de Goede 2005;Ho 2009;Ouroussoff 2010;Zaloom 2004). Instead, it comprises a heterogeneous set of practices that suggest possible modes of existence for the geological matter observed while it excludes others.…”
Section: The Substance Of Speculationmentioning
confidence: 95%
“…Since its inception, petroleum exploration has combined the bold assessments of oilmen with the speculative fantasies of urban financiers and the hypothetical inferences of a new breed of geoscientists in what an oil executive of the time called "the gamble of drilling for oil" (Zimmermann 1933, 500;Lucier 2008). Speculation, in this sense, exceeds its narrower, contemporary definition of a type of behavior pertaining exclusively to the domain of finance (de Goede 2005;Ho 2009;Ouroussoff 2010;Zaloom 2004). Instead, it comprises a heterogeneous set of practices that suggest possible modes of existence for the geological matter observed while it excludes others.…”
Section: The Substance Of Speculationmentioning
confidence: 95%
“…As recent anthropological research has shown, the gender dimension of financial markets should not simply be viewed in terms of political concerns about gender discrimination, but actually touches on more fundamental aspects of human social organization. The neutralized notion of risk in the pure theory blocks the view on the fact that trading is a highly intensive emotional experience, and that risk taking is a process that encompasses the entire spectrum of bodily experiences, especially in trading pits where traders gather collectively (Zaloom, 2004). In these contexts, the abstract notion of information processing on markets corresponds to a dense and intensive interaction among physically close, mostly male individuals, who have to use all means to signal their engagement of risk taking, and who have to decode emotional signals sent by others.…”
Section: Implications For the Theory Of Financementioning
confidence: 99%
“…With the intervening variable of identity, even unknown individuals might obtain identities which make them 'familiar', such that group-related mechanisms supporting cooperation may be triggered into operation. For example, traders at different financial centers have group identities, which are related with particular reputations (Zaloom, 2004).…”
Section: Implications For the Theory Of Financementioning
confidence: 99%
“…Voor niet weinigen van ons is het moment van gevaar, waarin het aankomt op onze instincten en veel geoefende vaardigheden, datgene wat het leven de moeite waard maakt. Fascinerend zijn dan ook de antropologische beschrijvingen van financiële handelaren die, als moderne alchemisten, risico's weten om te smeden in goud (Zaloom, 2004). De adrenaline, de krijg, de test der karakters, waarmee dit bijna mythische proces gepaard gaat, verdient het om onderdak te vinden in het dominante spreken over risico's, ook al vereist dat een diametraal tegenovergestelde normatieve bezetting van het risicobegrip.…”
Section: Figuur 65 Handelaren Op De Beurs Van Wall Streetunclassified